Peran Dosen Dalam Manajemen Sarana Dan Prasarana Di Institut Keguruan Dan Ilmu Pendidikan Kalimantan Timur - Nurul Hidayah; Okky Oktavia O'liezeth; Asri Ainurisa; Muhammad Amir Masruhim; Nurlaili; Akhmadianor (CV. Multi Kreasi Media, 2023)
Good management of facilities and infrastructure is expected to create a clean, neat, and beautiful university environment, thereby creating a pleasant atmosphere for both lecturers and students to be on campus. This Field Experience Practice (PPL) activity aims to explore more deeply the role of lecturers in the management of facilities and infrastructure at IKIP PGRI Kalimantan Timur. The methods used in this PPL activity include briefing, field observation, data processing, report writing, and article publication. Through this PPL activity, students are expected to directly observe the implementation of the theories learned during lectures, so that their knowledge of facilities and infrastructure management goes beyond theory to include real-world practice.